C18‐bound porous silica monolith particles as a low‐cost high‐performance liquid chromatography stationary phase with an excellent chromatographic performance. Issue 23 (21st October 2014) - Ali, Faiz; Cheong, Won Jo
<x xml:space="preserve">Abstract</x> Ground porous silica monolith particles with an average particle size of 2.34 μm and large pores (363 Å) exhibiting excellent chromatographic performance have been synthesized on a relatively large scale by a sophisticated sol–gel procedure. The particle size distribution was rather broad, and the d(0.1)/d(0.9) ratio was 0.14. The resultant silica monolith particles were chemically modified with chlorodimethyloctadecylsilane and end‐capped with a mixture of hexamethyldisilazane and chlorotrimethylsilane. Very good separation efficiency (185 000/m) and chromatographic resolution were achieved when the C18‐bound phase was evaluated for a test mixture of five benzene derivatives after packing in a stainless‐steel column (1.0 mm × 150 mm). The optimized elution conditions were found to be 70:30 v/v acetonitrile/water with 0.1% trifluoroacetic acid at a flow rate of 25 μL/min. The column was also evaluated for fast analysis at a flow rate of 100 μL/min, and all the five analytes were eluted within 3.5 min with reasonable efficiency (ca. 60 000/m) and resolution. The strategy of using particles with reduced particle size and large pores (363 Å) combined with C18 modification in addition to partial‐monolithic architecture has resulted in a useful stationary phase (C18‐bound silica monolith particles) of low production cost showing excellent chromatographic performance.